DIGITAL ETHICS PERCEPTION OF STARKI’ STUDENTS DURING THE COVID-19 ENDEMIC - Pamungkas, Petrus Dwi Ananto; Oetomo, Robertus Koesmaryanto; Septianingsih, Nithania (STKIP PGRI Tulungagung, 2024)
Entering the Covid-19 endemic period, the learning process at the Tarakanita College of Communication and Secretary (STARKI) has been carried out face to face between lecturers and students. Students' abilities in using digital media have increased. It's just that the problem is student ethics in using digital media. Based on several problems, such as the many screenshots of private conversations circulating in social media groups and uploading photos with other people without permission, research was conducted to determine the digital ethics index of STARKI students. Through descriptive quantitative research methods using the Proportionate Stratified Random Sampling technique, 196 people were obtained as respondents. From the results of the questionnaire, it can be explained that the digital ethics index for STARKI students for the 2022/2023 academic year is 79.23, which is included in the high category. This means that STARKI students understand to support government programs to prevent the spread of hate speech which often occurs in digital media by not inviting other people to comment negatively on digital media. However, there are still some STARKI students who still upload photos with other people without permission, still spontaneously upload photos of accidents, without permission still include other people in groups and even mark other people as friends, and share screenshots of private conversations via digital media. Thus, STARKI students' understanding of digital ethics still needs to be improved further until it reaches the maximum index.